Spare Parts Inventory Management System in an Automotive Downstream Supply Chain Network A Case Study - Gill, Salwinder Singh (My University, 2014)
The purpose of this study was to determine and validate the order point system in spare parts inventory management system (SPIMS) in the supply chain of an automotive organization. The objective was to control for costs. A SPIMS as proposed by Nagarur et al. (1994) was adopted after due deliberations with regards to the alignment between the SPIMS of the dealers of the automotive manufacturing organization and that proposed by the dealers. The SPIMS of the entire dealer network was studied; a critical analysis of SPIMS was carried out to ascertain the parity in the operational aspects of the system. It was observed that across the dealers the SPIMS was same and no modifications or customizations had been carried out, during analysis it was also observed to manage the SPIMS had been sponsored by the parent company. The model proposed by Nagarur et al. (1994) was also validated by using actual data of last three years collected over a period of six months. The order points were used to validate the model, and results were improved from the actual system followed by dealers. Also, the proposed model by Nagarur et al. (1994) was compared with the theoretical model of order point.
ME, MED
Keywords: Chain Network; Spare Parts Inventory Management